Interaction with a kinetic folded surface - Osório, F.; Paio, A.; Oliveira, S. (ECAADe 2014: Proceedings of the 32rd International Conference on Education and Research in Computer Aided Architectural Design in Europe, 2014)
Kinetic systems offers new perspectives and design innovation in research and practice. These systems have been used by architects as an approach that embeds computation intelligence to create flexible and adaptable architectural spaces according to users changing needs and desires as a way to respond to an increasingly technological society. The presented research attempts to answer to this question based on the results of a multidisciplinary on-going work developed at digital fabrication laboratory Vitruvius Fablab-IUL in Lisbon. The main goal is to explore the transformation of the shape of a construction by mechanisms which allow adaptation either to environmental conditions or to the needs of the user. This paper reports the initial development of a kinetic system based on an origami foldable surface actuated by a user. The user can manipulate a small scale model of the surface and evaluate at all times if it is achieving the desired geometry